Hubungan Spiritual Well-Being dengan Kualitas Hidup pada Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis: Studi Korelasi: The Relationship of Spiritual Well-Being with Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Correlational Study - Fitri Mailani; Natasha Melani Ardian; Rahmi Muthia (NERS Jurnal Keperawatan, 2024)
The quality of life in patients with chronic kidney disease undergoing hemodialysis needs to be improved due to the psychological pressure and adaptation to new lifestyle habits required by these patients. High levels of spiritual well-being are one of the strategies to enhance the quality of life in patients undergoing hemodialysis. This study aims to examine the relationship between spiritual well-being and quality of life in patients with chronic kidney disease undergoing hemodialysis. A correlational research design with a cross-sectional approach was employed in this study. A total of 111 respondents were selected using an accidental sampling technique. The instruments used in this study included a demographic questionnaire, the Spiritual Well-Being Scale, and the kidney disease and Quality of Life-36 questionnaire. Data were processed using descriptive statistics and Pearson correlation tests. The results indicated an average score of 97.39±8.32 for spiritual well-being, which falls within the moderate category, while quality of life was also in the moderate category with an average score of 48.05±7.90. A significant positive correlation with moderate strength was found between spiritual well-being and quality of life in patients with chronic kidney disease undergoing hemodialysis (p=0.000; r=0.417). It is recommended that nurses provide education and interventions such as writing therapy and involve the patients' families in the care process to provide emotional support, thereby improving spiritual well-being and quality of life in patients undergoing hemodialysis.